2009
DOI: 10.1051/0004-6361/200811580
|View full text |Cite
|
Sign up to set email alerts
|

High-energy characteristics of the schizophrenic pulsar PSR J1846-0258 in Kes 75

Abstract: Aims. PSR J1846−0258 is a young rotation-powered pulsar with one of the highest surface magnetic field strengths, located in the centre of SN-remnant Kes-75. In June 2006 a magnetar-like outburst took place. Using multi-year RXTE and INTEGRAL observations covering the epoch of the outburst, we aim to study the temporal and spectral characteristics of PSR J1846−0258 over a broad ∼3-300 keV energy range to derive constraints on theoretical scenarios aiming to explain this schizophrenic behaviour. Methods. We exp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
82
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(94 citation statements)
references
References 51 publications
11
82
1
Order By: Relevance
“…It was there found that a glitch with fractional change of period |∆P|/P ∼ (1.73-2.2) × 10 −6 could explain the outburst of 2006. This theoretical result is in full agreement with the observational analysis by Kuiper & Hermsen (2009), who showed that indeed a major glitch with |∆P|/P ∼ (2-4.4) × 10 −6 is associated with the outburst. Very recently, Archibald et al (2016) reported another example of an X-ray outburst from a radio pulsar, PSR J1119-6127, which also has L X <Ė rot .…”
Section: Glitches and Bursts In Sgrs/axpssupporting
confidence: 91%
“…It was there found that a glitch with fractional change of period |∆P|/P ∼ (1.73-2.2) × 10 −6 could explain the outburst of 2006. This theoretical result is in full agreement with the observational analysis by Kuiper & Hermsen (2009), who showed that indeed a major glitch with |∆P|/P ∼ (2-4.4) × 10 −6 is associated with the outburst. Very recently, Archibald et al (2016) reported another example of an X-ray outburst from a radio pulsar, PSR J1119-6127, which also has L X <Ė rot .…”
Section: Glitches and Bursts In Sgrs/axpssupporting
confidence: 91%
“…In view of the possible NS rotation-power nature of PSR J1846-0258, Malheiro et al [8] assumed that the outburst with energy (3.8-4.8) × 10 41 erg [20] was triggered by a glitch in the NS, and found that a glitch of |∆P |/P ∼ (1.73-2.2) × 10 −6 could explain the outburst of 2006. This theoretical result is in full agreement with the observational analysis of [21], who showed that indeed a major glitch with |∆P |/P ∼ (2-4.4) × 10 −6 occurred.…”
Section: Glitches and Burstssupporting
confidence: 91%
“…From this set of nine sources, the only glitch detected was the one of PSR J1846-0258 in June 2006 [21], whose observed value of |∆P |/P is shown with the gray-shaded area in these plots. Indeed a minimum mass for the NS can be established for this source by requesting that 1) the entire moment of inertia is involved in the glitch and 2) that the theoretical value of |∆P |/P coincides with the observed value: we obtain M min = 0.72 M ⊙ and M min = 0.61 M ⊙ for the global and local charge neutrality cases, respectively.…”
Section: Glitches and Burstsmentioning
confidence: 99%
“…The bursting activity was accompanied by a large spin-up glitch and marked the start of an enhancement in the pulsed X-ray flux which lasted about one month [121]. Spectral and flux variations associated with this event were seen also in the hard X-ray range [110]. All these phenomena are typical of magnetars.…”
Section: Magnetars With Low External Fieldmentioning
confidence: 87%